Pengaruh Citra Merek dan Kualitas Produk terhadap Kepuasan Pelanggan melalui Nilai Pelanggan - Ru'yatul Hilal; Rivera Silitonga (Human Capital Development, 2022)
This study aims to determine the effect of brand image and product quality on customer satisfaction through customer value at Loko Café Pasar Senen. The sample in this study were 197 respondents. The sampling technique used in this research is purposive sampling. This study uses quantitative descriptive methods by conducting survey research based on data by distributing questionnaires to respondents and researchers using path analysis methods. The researcher uses the quantitative descriptive method by analyzing the data using IBM SPSS Statistics 25. The results of research conducted by Loko Café Pasar Senen show that product quality has a significant effect on customer value. Brand Image has a significant effect on Customer Value. Product Quality and Customer Value have a significant effect on Customer Satisfaction. Brand Image has a significant effect on Customer Satisfaction. Brand Image has an indirect effect on Customer Satisfaction through Customer Value with a contribution of 0.038. Product quality has an indirect effect on customer satisfaction through customer value with a contribution of 0.115.